Determination of IC50 values of anticancer drugs on cells by D2O – single cell Raman spectroscopy. Issue 14 (26th January 2022) - Lv, Wanxue; Fu, Boqiang; Li, Manli; Kang, Yu; Bai, Shouli; Lu, Chao
Abstract : A simple, sensitive and repeatable D2 O-single cell Raman spectroscopy method was established to quantify the IC50 values of anticancer drugs by detecting C–D/(C–D + C–H) Raman peak area ratios after H and D exchange occurs in cell metabolism. Abstract : A simple, sensitive and repeatable D2 O-single cell Raman spectroscopy method is developed to quantify the inhibitory activity of anticancer drugs on cancer cell metabolism. The IC50 values obtained from A549 cells incubated with cisplatin and taxol are comparable with results of CCK-8 and ATP luminescent cell viability assays.